Control of industrial processes: contributions for analysis and implementation of controllers for processes with dead time, constraints, and modeling errors - Silva, Lucian Ribeiro da (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2023.